2014
DOI: 10.1039/c3cc47336h
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free nitro-carbocyclization of activated alkenes: a direct approach to synthesize oxindoles by cascade C–N and C–C bond formation

Abstract: A novel and direct metal-free nitro-carbocyclization of activated alkenes leading to valuable nitro-containing oxindoles via cascade C-N and C-C bond formation has been developed. The mechanistic study indicates that the initial NO and NO2 radical addition and the following C-H functionalization processes are involved in this transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 169 publications
(49 citation statements)
references
References 51 publications
2
47
0
Order By: Relevance
“…[9] Proposed reaction mechanisms based on the above results [9] and previous reports [6-8, 11, 12] are shown in Scheme 2. Initially, addition of NO 2 , which is generated in situ from tBuONO, [8,11,12] to the carbon-carbon double bond of the 1,7enyne 1 a gives alkyl radical intermediate A, which cyclizes to form intermediate B. The reaction of intermediate B with NO or NO 2 affords the corresponding intermediates C and C', which was supported by HRMS analysis.…”
Section: Methodsmentioning
confidence: 82%
See 2 more Smart Citations
“…[9] Proposed reaction mechanisms based on the above results [9] and previous reports [6-8, 11, 12] are shown in Scheme 2. Initially, addition of NO 2 , which is generated in situ from tBuONO, [8,11,12] to the carbon-carbon double bond of the 1,7enyne 1 a gives alkyl radical intermediate A, which cyclizes to form intermediate B. The reaction of intermediate B with NO or NO 2 affords the corresponding intermediates C and C', which was supported by HRMS analysis.…”
Section: Methodsmentioning
confidence: 82%
“…It has been reported that 2,2,6,6-tetramethylpiperidin-1-yl)oxy (TEMPO), a radical initiator, proved beneficial in some nitration reactions using tBuONO. [8] However, the presence of TEMPO suppressed the current reaction (entries 4 and 5): the yield of product 2 a decreased from 78 % to 67 % with 20 mol % TEMPO and to 53 % with 100 mol % TEMPO. Notably, a good yield was even achieved under N 2 atmosphere when DMSO was purged with N 2 (entry 6).…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…17 The transformation has a large substrate scope and allows the formation of biologically valuable compounds. 8-Methylquinolines are selectively nitrated through sp 3 C-H activation in the presence of catalytic amounts of palladium acetate in moderate to good yields (eq 13).…”
Section: Phmentioning
confidence: 99%
“…As a part of our continuing interest in the metal-free C-H functionalization/cyclization reactions. 15, 16 Herein we present an operationally simple and highly efficient cyanoisopropylation/ arylation without using any metal catalysts and additional oxidants, thus becoming a powerful alternative for accessing cyanocontaining oxindoles in a direct manner. Compared with previous reports, the significance of the present finding is twofold: (1) This transformation exhibits good generality: the substrate scope is not only applicable to N-arylacrylamides, but also to N-alkyl-N-(arylsulfonyl)acrylamides.…”
Section: Introductionmentioning
confidence: 99%